PHYTOCHEMICAL SCREENING AND INVITRO ANTI-INFLAMATORY ACTIVITY OF ETHANOLIC EXTRACT OF Centella asiatica (World Journal of Current Medical and Pharmaceutical Research, 2020)
In ayurvedic medicine Centella asiatica is a valuable medicinal herbaceous creeper which has been valued for hundreds of years. Phytochemical analysis of Centella asiatica (Apiaceae) plant extracts revealed the presence of varied biochemical compounds like alkaloids, flavonoids, glycosides, phenolic compounds, triterpenoids and saponin etc. Since phenolic compounds, triterpenoids and flavonoids have remarkable anti-inflammatory, anti-arthritic and antioxidant activities, so our present work aims at evaluating the in vitro anti-inflammatory activity by Human Red Blood Cell (HRBC) membrane stabilization. To measure the anti-inflammatory activity, the inhibition of hypotonicity induced HRBC membrane lysis was used. The percentage Haemolysis was experimented from concentration of 50µg/ml to 2000µg/ml and the values reduced from 32.25% to 5.02%, on the other hand percentage Stabilisation in the same concentration range increased from 67.74% to 94.97%. Diclofenac sodium was used as the standard drug and the same experiment conducted in the same concentration range and the values of percentage haemolysis reduced from 47.18% to 1.24% and the percentage stabilisation increased from 52.81% to 98.76%. The results show that the extracts of Centella asiatica exhibited anti-inflammatory activities. Centella asiatica may be a profusely branched prostate herb consisting of active principles like Vallarine, Asiaticoside, Sitosterol, Tannins, Oxy asiaticoside. Asiaticoside is used in the treatment of leprosy. Sitosterol and tannin possess antiprotozoal and spasmolytic property. According to Siddha literature, the leaves of Centella asiatica are used for the treatment of syphilis, elephantiasis, all kinds of fever, abdominal disorder of children and hydrocele and these features are highlighted in this article.